2022
DOI: 10.3390/ijerph19052778
|View full text |Cite
|
Sign up to set email alerts
|

Gastronomy Tourism and Well-Being: Evidence from Taiwan and Catalonia Michelin-Starred Restaurants

Abstract: In the tourism and hospitality industry, ensuring the well-being of visitors is essential to achieving a competitive tourist destination. This objective is even more pressing in the gastronomy sector. Surprisingly, the scientific literature on this topic is scarce and relies on questionnaire surveys and interviews as a data source. After scrutinizing the 13 articles on gastronomy tourism and well-being indexed in the Web of Science or in Scopus, this study proposes two new lines of research interrelated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 108 publications
0
13
0
3
Order By: Relevance
“…In the research, the effect of individuals' experiences at the gastronomy festival on memorable experiences can make a theoretical contribution to future research. Since the evaluation of the effect of hedonic and subjective well-being on loyalty and behavioral intention, which is discussed within the scope of the study, is handled through the gastronomy festival, it is thought that the theoretical deficiency in the researches in this field will be eliminated (Yılmaz, 2020;Kesgin et al, 2022;Lin et al, 2022;Kesgin, 2023). Therefore, this study makes an important theoretical contribution to the gap in the relevant literature in terms of determining the effect of individuals' memorable experiences and well-being on behavioral intentions at gastronomy festivals.…”
Section: Hedonic and Eudaimonicmentioning
confidence: 99%
“…In the research, the effect of individuals' experiences at the gastronomy festival on memorable experiences can make a theoretical contribution to future research. Since the evaluation of the effect of hedonic and subjective well-being on loyalty and behavioral intention, which is discussed within the scope of the study, is handled through the gastronomy festival, it is thought that the theoretical deficiency in the researches in this field will be eliminated (Yılmaz, 2020;Kesgin et al, 2022;Lin et al, 2022;Kesgin, 2023). Therefore, this study makes an important theoretical contribution to the gap in the relevant literature in terms of determining the effect of individuals' memorable experiences and well-being on behavioral intentions at gastronomy festivals.…”
Section: Hedonic and Eudaimonicmentioning
confidence: 99%
“…Este enfoque subraya la importancia de la educación en la formación de profesionales capacitados para la industria gastronómica. Lin et al (2022) investigaron cómo el turismo gastronómico influye en el bienestar de los visitantes. Utilizando revisiones en línea, exploraron el bienestar subjetivo que se deriva de experiencias gastronómicas de calidad, poniendo de relieve la importancia de la percepción del cliente en la evaluación de los restaurantes.…”
Section: Estado Del Arteunclassified
“…Tourists' food experiences are highly related to tourists' satisfaction and subjective well-being [ 59 ]. Tourists' well-being is derived from their high-quality food experiences [ 16 , 29 , 31 , 69 ] and memories of related food experiences [ 28 , 45 , 70 ]. Liu et al [ 71 ] conducted a survey of 497 tourists in Guangzhou, China and found that tourists' perceived value of destination food has a significant positive effect on tourists' subjective well-being.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%